Projeto ético político do serviço social: tensões e dilemas de um projeto em execução - Silva, Kelly Samara do Nascimento (2014)
This dissertation presents the product of master course at the Federal University of Paraíba and is focused on discussion of the ethical-political project of the profession of social service. This thesis will try to seize the discussions about the categories that guide the ethical-political project of social service seeking the historical and theoretical determinants, analyzing how the introduction, from the ethical-political project of social service, a direction based on the critical perspective was seized and incorporated in the category in their academic and intellectual production. The present study focuses on the theoretical analysis of the production of social service researchers, and beyond, to discuss the ethical-political project and the categories that surround it, in the analysis of corporate and professional projects with José Paulo Netto, Marcelo Braz and Maria Beatriz Abramides, among others. Also will use additional sources which can support the understanding of the components that guide the ethicalpolitical project and its dimensions. The survey period runs from the first half of 2009 to the first half of 2010.